Trophic component in realization of the active rest in the stimulation of tissues processes. - Chodinow Wladimir Nikolaevich (Kharkov National Pedagogical University, 2011)
In the physiological mechanism of active rest interaction with physical training, a very important role is played by the stimulation of tissues processes in tired muscles. While a passive rest usage, the average of 51,8% of the work capacity is regained, as far as an active rest is concerned, about 59,7%. An increase of tiredness causes growth of the relative participation of the active rest in the stimulation of tissues processes.